Synthesis and Structural Analysis of Persuasive Antibacterial Agents and Enzyme Inhibitors Derived from 5-(1-(4-Tosyl)piperidin-4-yl)-1,3,4-oxadiazol-2-thiol - Aziz-ur-Rehman; Sattar, Almas; Abbasi, Muhammad Athar; Siddiqui, Sabahat Z.; Raza, M. Arslan; Ashraf, Muhammad; Nazir, Munibaanum; Ali Shah, Syed Adnan (Asian Journal of Chemistry, 2017)
Due to outstanding biological activities of 1,3,4-oxadiazole, a series of S-substituted derivatives of 5-[1-(4-tosyl)piperidin-4-yl]-1,3,4-oxadiazol-2-thiol (5a-f) was synthesized. The reaction of p-toluene sulfonyl chloride (a) with ethyl isonepacotate (b) produced ethyl 1-(4-tosyl)piperidin-4-carboxylate (1) which was successively converted to 1-(4-tosyl)piperidin-4-carbohydrazide (2) by hydrazine and 5-[1-(4-tosyl)piperidin-4-yl]-1,3,4-oxadiazol-2-thiol (3) by CS2 in the presence of KOH. The aimed compounds (5a-f) were synthesized by the reaction of compound 3 with different electrophiles in DMF using lithium hydride as catalyst. The structural confirmation was done by IR, 1H NMR & EI-MS spectral analysis. The synthesized compounds were screened against a-glucosidase enzyme and five Gram bacterial strains.